Beyond the Shoreline: Rethinking Coastal Futures of Fisheries-Based Communities Through Blue Entrepreneurial Ecosystems in Greece - Ierapetritis, Dimitrios G (Sustainability, 2025)
In the preceding two decades, blue entrepreneurship has emerged as a pivotal proposition for Europe’s coastal fishing communities, as these communities have sought to diversify and reinvigorate their local economies. The present paper seeks to shed light on the driving forces and obstacles to the development of blue entrepreneurship in fishing communities through an innovative entrepreneurial ecosystem approach. The results of a qualitative survey, conducted through a questionnaire addressed to representatives of 80 stakeholders (private companies, local authorities, development companies, Local Action Groups for Fisheries (FLAGs), organizations, NGOs, academic and research institutions) based in and around coastal fishing communities, are explored in order to identify the driving forces and barriers to the development of blue entrepreneurship. The research was conducted by selecting stakeholders from five distinct coastal regions of Greece. These regions are dependent on fishing and have local Community-Led Local Development (CLLD)/LEADER programs that were funded by the Operational Program Fisheries and Maritime Affairs 2014–2020 during the 2014–2020 programming period. Subsequently, adopting existing models through an entrepreneurial ecosystem approach, the driving forces and obstacles highlight the weaknesses of Greek blue entrepreneurial ecosystems in coastal fishing communities, focusing on the existing blue framework conditions and the existing blue systemic conditions. Finally, the primary conclusions of the research are emphasized, and policy proposals are advanced to encourage the establishment of blue entrepreneurial ecosystems in Greek coastal fishing areas.